A review of key tools for oil pipe blockage operation in gas wells under pressure. Issue 1 (March 2021) - Song, Chunyuan; Hu, Shoulin; He, Yunbin; Yang, Hai
Abstract: Blockage in tubing is an important guarantee for gas wells under pressure. The internal blockage is to close the channel inside the tubing through a sealing device, the pipe string can be lifted and lowered under pressure. In order to prevent natural gas from leaking through the tubing channel during well completion and string lifting operations, a plugging tool in the tubing is required to block the tubing channel, and the blockage is removed after the operation is completed to effectively control the pressure in the well. This article starts with the key tools related to internal plugging operations in Snubbing operation, introduces the basic principles of setting the internal plugging barriers when running the tubing string in completion operations, and introduces the key tools for internal plugging when the tubing runs in completion operations. The internal plugging method of the pipe string under pressure is introduced. The key tools (bridge plugs) and setting methods that have been matured or formed at home and abroad when the pipe string is lifted in workover are introduced. Well technology and key tool selection provide reference. Finally, we analyze and think about the domestically developed self-developed internal plugging tools for pressurized operations in my country. It is believed that internal clogging is not an isolated process of oil, gas, and water plugging, but is usually a process of multi-system construction processes working together. The key domestic tools and equipment also need to further improve their autonomous capabilities in terms of overall performance and stability, as well as intelligence.